2019
DOI: 10.1007/s10909-019-02248-w
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Principal Component Analysis for Outlier Identification in Messy Microcalorimeter Data

Abstract: A principal component analysis (PCA) of clean microcalorimeter pulse records can be a first step beyond statistically optimal linear filtering of pulses towards a fully nonlinear analysis. For PCA to be practical on spectrometers with hundreds of sensors, an automated identification of clean pulses is required. Robust forms of PCA are the subject of active research in machine learning. We examine a version known as coherence pursuit that is simple, fast, and well matched to the automatic identification of outl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the context of calorimetric signal processing, PCA-based methods have been shown to have resolution power superior to standard optimal filtering techniques under certain circumstances [9,10], with the leading PCA components used to estimate the energy of a pulse. Other studies have demonstrated the ability to perform outlier detection using PCA-based methods without having to rely on labeled training data like in supervised learning [11,12].…”
Section: Principal Component Analysismentioning
confidence: 99%
“…In the context of calorimetric signal processing, PCA-based methods have been shown to have resolution power superior to standard optimal filtering techniques under certain circumstances [9,10], with the leading PCA components used to estimate the energy of a pulse. Other studies have demonstrated the ability to perform outlier detection using PCA-based methods without having to rely on labeled training data like in supervised learning [11,12].…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The main objectives are mitigating nonlinearity of the detector output, reconstructing single events from pile-up events, lowering the threshold for unresolved pile-up, and detecting outliers. Most approaches are based on either (modified) optimal filtering techniques [15,16] or on principal component analysis [17][18][19][20][21]. While these methods show promising results, in this study we focus on arithmetically simple approaches as we aim for a fast online data reduction.…”
Section: Data Reductionmentioning
confidence: 99%
“…In the context of calorimetric signal processing, PCA-based methods have been shown to have resolution power superior to standard optimal filtering techniques under certain circumstances [9,10], with the leading PCA components used to estimate the energy of a pulse. Other studies have demonstrated the ability to perform outlier detection using PCA-based methods without having to rely on labeled training data like in supervised learning [11,12].…”
Section: Principal Component Analysismentioning
confidence: 99%